The Impact of Water Resource Utilization on Afghanistan's International Relations: Challenges and Opportunities for Transboundary Water Management - Wafa, Noorani; Mazloum Yar, Fayaz Gul (Journal Of Social Science (JoSS), 2024)
This research examines the impact of water resources management on Afghanistan's international relations, particularly with neighboring countries such as Iran, Pakistan and Tajikistan. As a landlocked country, Afghanistan is highly dependent on water resources, which are vital to its political, economic and social stability. The purpose of this study is to analyze the opportunities and challenges associated with water resources management and the importance of international cooperation in this context. The research used a mixed approach, combining qualitative and quantitative methods. Data collection was conducted through semi-structured interviews with experts and stakeholders, as well as a survey to assess the views of local communities. Data analysis was conducted using statistical software such as SPSS and NVivo. The findings show that effective water resources management can reduce international tensions and improve Afghanistan's socio-economic conditions. In addition, the lack of international agreements can lead to discontent and recurrent tensions between Afghanistan and neighboring countries. The research also identified climate change as a significant factor affecting the availability of water resources. Effective management of water resources is not only important for Afghanistan's domestic stability, but also for its international relations. The research recommends the need for comprehensive international agreements and infrastructure development to improve sustainable water management and encourage regional cooperation.